Impact of various remineralizing agents on artificial white spot lesion on primary teeth-A comparative study - Abdulhamid Al Ghwainem (Wolters Kluwer Medknow Publications, 2023)
Aim: The aim of the current research was to assess the effectiveness of different remineralizing substances on artificial white spot lesions on deciduous teeth. Materials and Methods: 45 deciduous teeth without dental caries constituted the study group for this in vitro research. A 3 mm by 3 mm window of enamel was uncovered at the occluso-gingival midpoint of the coronal labial surface; an acid-resistant nail varnish was coated alongside the uncovered enamel surface of all specimens, employing vertical strokes. Demineralization was executed for the tenure of 72 hours at 37°C temperature in an incubator. The forty-five specimens, fifteen in each group, were assigned to the investigational groups plus a control group as: Group A: Control, Group B: Calcium sucrose phosphate (CaSP), Group C: Casein phosphopeptide-amorphous calcium phosphate-fluoride (CPP-ACPF). Microhardness tester was employed for testing the microhardness of the enamel surface using a Vickers diamond indenter laden with twenty-five milligrams for approximately ten seconds. Vickers hardness number (VHN) calculations for the microhardness were performed at baseline and on the fourteenth day. Results: The CPP-ACPF group exhibited greater mean microhardness value at 236.14 ± 2.12, in pursuit by CaSP group with a score of 231.98 ± 3.16 and then the control group at 220.22 ± 5.08. An extremely statistically significant difference was seen amid the groups. Conclusion: The current research arrived at a conclusion that both the remineralizing substances were certainly efficient in handling early dental caries, and additionally, casein phosphopeptide-amorphous calcium phosphate-fluoride (CPP-ACPF) was found highly efficient as a remineralizing substance, in pursuit by calcium sucrose phosphate (CaSP).